2014
DOI: 10.1158/0008-5472.can-13-1865
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium in Colonic Flora and Molecular Features of Colorectal Carcinoma

Abstract: Fusobacterium species are part of the gut microbiome in humans. Recent studies have identified over-representation of Fusobacterium in colorectal cancer (CRC) tissues but it is not yet clear whether this is pathogenic or simply an epiphenomenon. In this study, we evaluated the relationship between Fusobacterium status and molecular features in CRCs through quantitative real-time PCR in 149 CRC tissues, 89 adjacent normal appearing mucosae and 72 colonic mucosae from cancer-free individuals. Results were correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
319
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(367 citation statements)
references
References 35 publications
27
319
1
2
Order By: Relevance
“…Fusobacterium has been associated with colorectal tumors and adenomas in several recent studies. 27,31,[61][62][63][64][65] In the present study, Fusobacterium was significantly over represented in tumor compared to adjacent tissues in the Spanish cohort, while in the US, this phylum was more abundant in both tissues compared to the Spanish cohort, but enriched specifically in tumors in splenic flexure, sigmoid and rectum. More studies are needed to assess the biological significance of these results, which could be related to the ability of these microorganisms to form and maintain biofilms in specific locations of the large intestine as recently shown.…”
Section: Discussionsupporting
confidence: 40%
“…Fusobacterium has been associated with colorectal tumors and adenomas in several recent studies. 27,31,[61][62][63][64][65] In the present study, Fusobacterium was significantly over represented in tumor compared to adjacent tissues in the Spanish cohort, while in the US, this phylum was more abundant in both tissues compared to the Spanish cohort, but enriched specifically in tumors in splenic flexure, sigmoid and rectum. More studies are needed to assess the biological significance of these results, which could be related to the ability of these microorganisms to form and maintain biofilms in specific locations of the large intestine as recently shown.…”
Section: Discussionsupporting
confidence: 40%
“…During the past decade, an emerging notion that the contributions of the TME to carcinogenesis must be considered in the biology of neoplasms (16), revealing an important role of local tissue microenvironment involving in the formation of tumor-associated stroma in tumorigenesis. To date, several studies have found that altered tissue microenvironment has an effect on colorectal carcinogenesis, and epigenetic changes function as a key player in cellular response to the alteration of microenvironment (46)(47)(48), which are consistent with our results revealing the histologically altered morphologies of tissues with different distance to CRC lesions, loss of normal crypts and existence of many ACf in no. 3, however, tissues no.…”
Section: Discussionsupporting
confidence: 92%
“…Inter-patient heterogeneity in tumor immunity result from genetic background involved in carcinogenesis, such as mismatch repair gene deficiency and POLE mutation, and personal disease-modifying factors, such as composition of intestinal bacterial flora 15,16) , smoking status and pre-existing disease. These factors of inter-patient heterogeneity were previously evaluated by analyzing therapeutic response data, clustering analysis preceded by DNA microarray analysis, and whole exome sequencing which revealed DNA mutation load found in each patient ( Table 1) .…”
Section: Abstract Colorectal Cancer; Tumor Immunology; Immune Checkpmentioning
confidence: 99%